Case Report: Acute Onset Fear of Falling and Treatment With “Cognitive Physical Therapy” - Castro, Patricia; Vadera, Shree; Bancroft, Matthew James; Buttell, Joseph; Kaski, Diego (Frontiers in Neurology, 2021)
Fear of falling (FoF) is prevalent in older adults, especially those with previous falls, and typically starts insidiously. We present a 78-year-old woman with an abrupt onset FoF and no history of falls, balance problems, vertigo, oscillopsia, psychiatric or psychological issues to account for this. These cognitive changes led to a behavioural alteration of her gait that became slow and wide-based, with her gaze fixed on the floor. She began a tailored program of “Cognitive Physical Therapy (CPT)” combining cognitive behavioural therapy (CBT) and physical rehabilitation. 1 month later her 6 m walk time and steps were reduced by a 25 and 35%, respectively, and the stride length increased by 34%, with further improvement 2 months later. We postulate that the abrupt onset of symptoms triggered a central shift toward postural hypervigilance and anxiety, suppression of anticipatory (feed forward) postural adjustments (APA) leading to FoF. CPT improved objective gait parameters related to FoF and reduced postural anxiety suggesting that early diagnosis and prompt treatment may avoid chronic symptoms and social isolation.